2010
DOI: 10.1039/b925074c
|View full text |Cite
|
Sign up to set email alerts
|

Water adsorption in hydrophobic MOF channels

Abstract: We report an investigation of water adsorption in the hydrophobic metal-organic framework Al(OH)(1,4-naphthalenedicarboxylate) by means of molecular simulation. We show how simple molecular models allow us to reproduce the experimental isotherm, and how grand canonical Monte Carlo simulations can help elucidate the question of the thermodynamic nature of the adsorption transition, which turns out to be a continuous transition, though the experimental isotherm is quite steep. Moreover, we study the influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 45 publications
4
69
0
Order By: Relevance
“…They demonstrated that, at high water loading, the metal oxide cluster stabilizes a water cluster in its neighbourhood which promotes the ligand displacement (see also Ref. 65 for a theoretical discussion on the stability of MOFs in water). Such a mechanism may explain the presence of Zn-OH defects which are active in acid catalysis.…”
Section: Degradation Mechanismsmentioning
confidence: 99%
“…They demonstrated that, at high water loading, the metal oxide cluster stabilizes a water cluster in its neighbourhood which promotes the ligand displacement (see also Ref. 65 for a theoretical discussion on the stability of MOFs in water). Such a mechanism may explain the presence of Zn-OH defects which are active in acid catalysis.…”
Section: Degradation Mechanismsmentioning
confidence: 99%
“…In particular, grand canonical Monte Carlo simulation methods, taking place in the eponymous statistical ensemble, are now widely used and part of the standard molecular simulation toolbox for calculating thermodynamic adsorption properties in rigid materials. New Monte Carlo algorithms allow the simulation of systems that were considered impossible to study via computer simulations a few years ago (for instance long alkane chains, [85] halocarbon or aromatic molecules [86,87] and water [88,89] ). In most of these studies, a rigid framework is assumed for the adsorbent.…”
Section: The Case Of Adsorption In Nanoporous Materialsmentioning
confidence: 99%
“…Simulation studies by Coudert et al. also showed that water condensation was shifted to higher water vapour pressures when the pore size of Al(OH)(1,4‐NDC) was reduced by methylation of the naphthalene aromatic rings 19…”
mentioning
confidence: 98%
“…[18] Simulation studies by Coudert et al also showed that water condensation was shifted to higher water vapour pressures when the pore size of Al(OH)A C H T U N G T R E N N U N G (1, was reduced by methylation of the naphthalene aromatic rings. [19] In contrast to desolvated SNU-80, which was stable in saturated water vapour as well as in liquid water, the green crystals of as-synthesized SNU-80a became amorphous after being immersed in water for 6 h ( Figure S12 in the Supporting Information), and degraded to colourless powder after being immersed in water for 2 days, which was ascribed to the ligand teia by NMR spectroscopy. For a better understanding of this process, we conducted Grand Canonical Monte Carlo (GCMC) simulations for water adsorption in the framework of SNU-80a (see the Supporting Information).…”
mentioning
confidence: 99%